2021
DOI: 10.3390/jcm10143130
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Abnormalities Detected by CT in Asbestos-Exposed Subjects Are More Likely Associated to Age

Abstract: Objective: the aim of this study was to evaluate the association between interstitial lung abnormalities, asbestos exposure and age in a population of retired workers previously occupationally exposed to asbestos. Methods: previously occupationally exposed former workers to asbestos eligible for a survey conducted between 2003 and 2005 in four regions of France, underwent chest CT examinations and pulmonary function testing. Industrial hygienists evaluated asbestos exposure and calculated for each subject a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similarly, in secondary ILDs, studies have reported older age in ILDs associated with CTD compared to CTD without ILD ( 37 , 38 ), as well as in chronic HP compared to acute HP ( 39 ). In a recent study by Laurent et al ( 40 ), a significant positive correlation was found between definite or possible UIP patterns and age in individuals exposed to asbestos. However, previous studies have yielded inconsistent findings regarding age differences between patients with UIP and NSIP ( 30 , 41 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, in secondary ILDs, studies have reported older age in ILDs associated with CTD compared to CTD without ILD ( 37 , 38 ), as well as in chronic HP compared to acute HP ( 39 ). In a recent study by Laurent et al ( 40 ), a significant positive correlation was found between definite or possible UIP patterns and age in individuals exposed to asbestos. However, previous studies have yielded inconsistent findings regarding age differences between patients with UIP and NSIP ( 30 , 41 ).…”
Section: Discussionmentioning
confidence: 85%
“…Despite the heterogeneities, the clinical and laboratory data of patients with UIP from various causes display remarkable similarities, shedding light on the shared underlying mechanisms (37,38), as well as in chronic HP compared to acute HP (39). In a recent study by Laurent et al (40), a significant positive correlation was found between definite or possible UIP patterns and age in individuals exposed to asbestos. However, previous studies have yielded inconsistent findings regarding age differences between patients with UIP and NSIP (30, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Information on other asbestosrelated diseases such as plaques, pleurisy, or fibrosis have not been collected. However, while these signs may provide arguments for past exposure, they are rare, even among highly exposed subjects [43,44]. Finally, reliable environmental and geographic information on asbestos (from the natural environment or asbestos processing facilities) are not available in France, and could therefore not be assessed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…The role of asbestos in the development of lung cancer and pleural mesothelioma has been clearly demonstrated, even if one fifth of mesothelioma is not explained by an exposure to asbestos. The study by Laurent et al [ 10 ] was carried out on 2157 former workers previously professionally exposed to asbestos who underwent chest CT scans and pulmonary function tests in order to assess asbestos exposure and calculate a cumulative asbestos exposure index (CEI) for each subject. The aim was to evaluate the link between interstitial lung anomalies, asbestos exposure, and age in a population of retired workers previously occupationally exposed.…”
mentioning
confidence: 99%